Bahasa Jepang Sebagai Bahasa Asing -Pemahaman Pembelajar Terhadap Kala- - Gede Satya Hermawan (JLA (Jurnal Lingua Applicata), 2019)
In Indonesian to express time in the past, present, and future only indicated by time adverbs, and no conjugation in the verb. The first-year Japanese language education learners in the Ganesha  University of Education, when they began to understand tenses in Japanese, it was seen that the concept of tenses in Indonesian was interference. The not only verb conjugation in Japanese is an obstacle, but the understanding of concepts Japanese tenses has also become a problem for learners. This paper will explain to the understanding of first-year Japanese language learners when applied Japanese tenses. This research is experimental research, where learners will be given two sentences, and asked to explain the differences. If the learner understands the concept of the Japanese tenses, the learner will find the difference from the time of the event in the sentence. There were 22 learners first-year Japanese language learners who were the subjects of the research. The results obtained are the first-year Japanese language learners of the Ganesha University of Education,  most of whom have not shown a good understanding of the use of Japanese tenses, this is indicated by the number of learners who are right in explaining that there are four people from 22 learners.